2015
DOI: 10.1136/bmjopen-2015-008932
|View full text |Cite
|
Sign up to set email alerts
|

Trends in global clinical trial registration: an analysis of numbers of registered clinical trials in different parts of the world from 2004 to 2013

Abstract: ObjectivesTo analyse developments (and their causes) in the number and proportion of clinical trials that were registered in different parts of the world after the International Committee of Medical Journal Editors (ICMJE) announced in 2004 that it would require registration of clinical trials as a condition for publication.SettingThe International Clinical Trials Registry Platform (ICTRP).DesignThe ICTRP database was searched for all clinical trials that were registered up to 31 December 2013.ResultsThe ICTRP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
159
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(174 citation statements)
references
References 65 publications
6
159
1
3
Order By: Relevance
“…Although ClinicalTrials.gov continues to be the most useful data source, we found that duplication with other registries is increasing; a finding confirmed by a recent study on trends in global clinical trial registration on the national and regional registries searchable via the WHO's ICTRP 19 . Posting of summary results is now mandatory for interventional trials registered with the EU Clinical Trials Database (EudraCT) and completed on or after 21 July 2014 20 , and required retrospectively for trials completed before that date in accordance with specific timeframes 21 .…”
Section: Clinical Trial Transparency Of Recently Approved Medicinessupporting
confidence: 76%
“…Although ClinicalTrials.gov continues to be the most useful data source, we found that duplication with other registries is increasing; a finding confirmed by a recent study on trends in global clinical trial registration on the national and regional registries searchable via the WHO's ICTRP 19 . Posting of summary results is now mandatory for interventional trials registered with the EU Clinical Trials Database (EudraCT) and completed on or after 21 July 2014 20 , and required retrospectively for trials completed before that date in accordance with specific timeframes 21 .…”
Section: Clinical Trial Transparency Of Recently Approved Medicinessupporting
confidence: 76%
“…4 Thousands of clinical trials used to be conducted annually but the share Asia about 10% this number usually goes to East Asia, where the share of KSA is less than 0.5%. 5 In the past, conducting of these trials in the KSA usually as a relationship between pharmaceutical companies and the clinical researchers without rules and regulation until the SFDA intervene and give permission to create contract research organization (CRO) to work as a moderator between the clinical researchers and pharmaceutical companies in parallel with GCP guidelines. This is the case in Japan and South Korea where both countries started recently practicing clinical trials according to GCP standards.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, even in the re-gions where clinical trials are regulated and compulsory, laws tend to exclude all trial types, e.g., phase 1 trials and device trials. This can lead to a limitation in the number of phase 1 trials that are registered [35] .…”
Section: Discussionmentioning
confidence: 99%